Ultra Low Power Ionizing Dose Sensor Based on Complementary Fully Depleted MOS Transistors for Radiotherapy Application - Alcalde Bessia, F.; Flandre, D.; André, N.; Irazoqui, J.; Pérez, M.; Gómez Berisso, M.; Lipovetzky, J. (IEEE, 2019)
Fil: Alcalde Bessia, F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina